New developments in the treatment of acute bacterial skin and skin structure infections: considerations for the effective use of dalbavancin - Juul JJ; Mullins CF; Peppard WJ; Huang AM (Dove Medical Press, 2016)
Janelle J Juul, Caitlin F Mullins, William J Peppard, Angela M Huang Department of Pharmacy, Froedtert & the Medical College of Wisconsin, Milwaukee, WI, USA Abstract: Dalbavancin, an intravenous glycopeptide, was approved by the US Food and Drug Administration in May 2014 for use in adult patients with acute bacterial skin and skin structure infections. The recommended dosing regimen for effective use of dalbavancin is 1,000 mg followed by a 500 mg dose after 1 week. Two multinational, identically designed, non-inferiority trials, DISCOVER 1 and 2, demonstrated similar early clinical success with dalbavancin compared to vancomycin with an option to switch to oral linezolid. In a recently published non-inferiority trial, a single-dose regimen of dalbavancin was compared to the traditional two-dose administration and was found to have a non-inferior clinical response. In the aforementioned trials, dalbavancin was well tolerated, with patients experiencing transient adverse events of mild to moderate severity. The prolonged half-life, excellent skin and soft tissue penetration, bactericidal activity against Gram-positive bacteria including methicillin-resistant Staphylococcus aureus, and convenient dosing make dalbavancin a reasonable option for the treatment of acute bacterial skin and skin structure infections in adult patients who have tried and failed other therapies. Keywords: acute bacterial skin and skin structure infections, skin and soft tissue infections, dalbavancin, glycopeptide